2022
DOI: 10.1101/2022.01.02.474499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetically-linked simultaneous overexpression of multiple herbicide-metabolizing genes for broad-spectrum resistance in an agricultural weed Echinochloa phyllopogon

Abstract: The use of herbicides in agricultural fields has driven the evolution of weeds for resistance, causing a grave threat to the current agriculture. One big mystery of weed resistance involves multiple-herbicide resistance (MHR) concomitant to enhanced herbicide metabolism. Previous research unveiled that the overexpression of catalytically promiscuous cytochrome P450s underlies the metabolism-based cross-resistance in multiple species. However, the concept of activation of promiscuous enzymes does not fully acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 83 publications
(217 reference statements)
0
7
0
Order By: Relevance
“…However, given the low level resistance by CYP709C56 and the very narrow resistance spectrum by the similar gene CYP709C69 from E. phyllopogon (i.e. only resistant to diclofop‐methyl) (Suda et al., 2022), we consider CYP81Q32 to be a major gene conferring mesosulfuron‐methyl resistance in B. syzigachne .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the low level resistance by CYP709C56 and the very narrow resistance spectrum by the similar gene CYP709C69 from E. phyllopogon (i.e. only resistant to diclofop‐methyl) (Suda et al., 2022), we consider CYP81Q32 to be a major gene conferring mesosulfuron‐methyl resistance in B. syzigachne .…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the large numbers of P450 super family genes and the lack to date of well‐annotated weed genomes, progress in identifying such resistance genes in weedy plants has been slow. A few P450 genes have been recently identified and characterized in herbicide‐resistant weeds, including several CYP81As and CYP709C69 from Echinochloa phyllopogon (Dimaano et al., 2020; Guo et al., 2019; Iwakami et al., 2019; Iwakami, Endo, et al., 2014; Suda et al., 2022), CYP81A10v7 from Lolium rigidum (Han et al., 2020), CYP81A68 from Echinochloa crus‐galli (Pan et al., 2022), and CYP709C56 from Alopecurus aequalis (Zhao et al., 2022). Despite this recent emerging body of work in identification of weed P450s conferring herbicide resistance, little has been achieved in understanding molecular mechanisms regulating the expression of these P450s.…”
Section: Introductionmentioning
confidence: 99%
“…36 CYP709C69 from E. phyllopogon confers resistance to ACCase-inhibiting herbicide diclofop-methyl. 55 Apart from CYP709, a CYP704A177 gene from Beckmannia syzigachne has recently been identified to confer resistance to ALS-inhibiting herbicides pyroxsulam and bispyribac-sodium. 56 Apparently, all of these currently identified CYP709 and CYP704 offer a narrow resistance spectrum relative to CYP81As.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that simultaneous overexpression of multiple herbicidemetabolizing genes of (CYP81A12/21 and CYP709C69) enhances and broadens the metabolic resistance profile in E. phyllopogon, and these genes are all under a single regulation mechanism. 55 Recently, two wild radish populations with a 12 year use history of HPPD-inhibiting herbicides showed relatively high levels of resistance (about 10-fold) to mesotrione, pyrasulfotole, and topramezone. 16 Because the resistance in the R wild radish population investigated in our study was not directly selected by HPPD-inhibiting herbicides and the resistance level is modest, the identified NTSR genes can be different from those involved in a higher level of resistance in other wild radish populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation